Pembangunan Rumah Pompa Air Sebagai Upaya Untuk Meningkatkan Efektivitas Pengairan Sawah Di Desa Sukomulyo - Muhammad Maulana Muhson; Suhendri al farisi; Ahmad kasyif syarof; Muhammad maulidi; Ahmad Yudi Prasetya; Tegar Ezha Pratama; Muhammad A’la Muhibbin; Ariya Rifqi Al Baihaqi; Awwalia Fitrotin Izza (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
Sukomulyo is a village located in Kaliwungu Selatan District, Kendal Regency, most of whose residents work as farmers. The rice fields in Sukomulyo village are irrigated using river water which is taken directly from the Waridin River with a diesel water pump. The process of irrigating the rice fields takes a long time, so the water pumps are simply left alone by the farmers because they are doing other activities. Often farmers forget to turn off the water pumps they turn on, resulting in wasteful use of river water and fuel. When the dry season arrives, there could be a decrease in the river water discharge to the ground which has the potential to result in farmers not being able to irrigate their rice fields with water. To overcome this problem, the Sukomulyo farmer group in collaboration with the PPL (Agricultural Extension Worker) of Kaliwungu Selatan District built a water pump house which is used for their rice field irrigation needs. With the construction of the water pump house, it is hoped that it can irrigate farmers' rice fields during the dry season and can increase agricultural production in Sukomulyo Village and can reduce farmers' worries when the river water does not flow